The Effect of Dhikr Therapy on Increasing The Meaningfulness of Life in Students at The Satu Amal Indonesia Foundation - Rayuni Larasaty.AZ; Putri Wulandari; Muhammad Iqbal Alhadii (CV. Era Digital Nusantara, 2024)
This study aims to determine the effect of dhikr therapy on increasing the meaningfulness of life experienced by students who are members of the Satu Amal Indonesia foundation. This study uses a one-group pretest-posttest design method because it can compare conditions before and after being given treatment. With various treatments carried out for 7 days or one week on WhatsApp Group. This study presents the results of the effectiveness test of dhikr therapy on the meaningfulness of life using the